Ecofriendly green synthesis of ZnO nanostructures using Artabotrys Hexapetalu and Bambusa Vulgaris plant extract and investigation on their photocatalytic and antibacterial activity. (6th September 2019) - Shanavas, S; Duraimurugan, J; Kumar, G Suresh; Ramesh, R; Acevedo, R; Anbarasan, P M; Maadeswaran, P
Abstract: In this present study, we report the green synthesis of ZnO nanoparticles by plant extracts mediated co-precipitation method using environmental friendly Artabotrys hexapetalus and Bambusa vulgaris plant extract as a reducing agent. The formation of hexagonal wurtzite crystalline phase ZnO was confirmed by x-ray diffraction results. The study on optical properties of these nanoparticles reveals that both Artabotrys hexapetalu and Bambusa vulgaris plant extract mediated ZnO nanostructures are active in the visible region. The morphological investigation demonstrates that ZnO nanoparticles formed with both spherical and rod-like structures having a particle size of about 20-30 nm in diameter. The functional group analysis by FTIR study indicated the presence of biomolecules as the stabilizing agent around ZnO nanoparticles. The photocatalytic degradation performance of ZnO nanoparticles was examinedusing Rhodamine B (RhB) as a model dye under visible light irradiation. The photocatalytic degradation of RhB molecules follows pseudo first-order kinetic model and the degradation rate constant is found to be 1.4 × 10 –2 min −1 and 1.21 × 10 –2 min −1 for AHZnO and BVZnO nanoparticles, respectively. The antibacterial properties of prepared ZnO nanoparticles were examined towards the inhabitation of S treptococcus (gram positive) and Serratia (gram negative) pathogens. Hence, the current research clearly indicates that both AHZnO and BVZnO nanoparticles has the potential for both photocatalytic and antibacterial applications.